Char peoples production practices and livelihood status: An economic study in Mymensingh district - Uddin, MT; Dhar, AR (Journal of the Bangladesh Agricultural University, 2017)
The study was conducted to explore the production practices followed by the farmers in char areas of two Upazilas of Mymensingh district, and determine their livelihood status considering natural calamities. A total of 120 farmers were selected randomly for data collection. Data were analyzed with a combination of descriptive statistics, mathematical and statistical techniques. The results of the descriptive statistics showed that majority of the farmers were engaged in C-L-HA farming system (52.5 percent) which was followed by C-L-P and C-P-HA farming systems (32.0 and 15.5 percent, respectively). Profitability analysis reveals that crop, livestock and poultry were found profitable under C-L-P farming system, where homestead and agroforestry was found profitable under C-L-HA farming system. The differences in productivity of agricultural enterprises between char land and main land were found significant in most of the cases. About 65.0 percent of farmers average annual income was earned from farming activities and 35.0 percent was from non-farming activities. Food security indices indicated that average per capita daily calorie intake of the households (2068.9 kcal for food secure households and 1482.4 kcal for food insecure households) was still below the national average level of 2122 kcal. Livelihood status of the char dwellers incorporating farmers asset possession, activities and strategies, well being, and external policies and institutions was improved by their production practices. Applying severity ranking model (SRM) and agreement index (AI), river erosion, flood, cyclone and drought were found most frequent in the study areas that caused severe damage to respondents cultivable land, assets, agricultural enterprises and basic necessities. The study recommended that input subsidy and output price support, and social safety net programmes should be properly implemented by the government to protect the char dwellers in crisis period and enhance their livelihood condition. J. Bangladesh Agril. Univ. 15(1): 73-86, January 2017